Organizational Resilience in MSME Sustainability: Roles of Entrepreneurial Orientation, Internal Capabilities and Business Environment - Natalia Magdalena Rafu Mamulak; Erma Suryani; Jerry Dwi Trijoyo Purnomo (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study examined how entrepreneurial orientation, internal capabilities, and business environment influence MSME operational sustainability through organizational resilience. Using a quantitative, explanatory, cross-sectional survey design, data were collected from 331 owners or managers of traditional weaving MSMEs in Nusa Tenggara Timur, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling to test direct and indirect relationships among the study constructs. The results show that entrepreneurial orientation and internal capabilities did not have significant direct effects on operational sustainability. However, both variables had significant positive effects on organizational resilience, which in turn significantly enhanced operational sustainability. The business environment had the strongest effect in the model, exerting both a significant direct effect on operational sustainability and an indirect effect through organizational resilience. These findings indicate that organizational resilience functions as the key mediating capability through which strategic posture and internal strengths are translated into sustained business operations. The study extends MSME sustainability research by moving beyond direct-effect explanations and demonstrating the importance of resilience as an organizational mechanism. Practically, the findings suggest that resilience-oriented interventions, combined with improvements in external business conditions, are essential for strengthening the viability of culturally embedded and structurally constrained MSMEs in Eastern Indonesia.